2016
DOI: 10.5455/ijmsph.2016.22072015109
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis C in renal failure patients on maintenance hemodialysis - Study in a tertiary care hospital - Western India

Abstract: Background: Hepatitis C is endemic in most parts of the world. It is a blood borne infection, which has a significant impact in treatment and outcome of renal failure patients undergoing dialysis. Objective:To determine the seroprevalence of hepatitis C in renal failure patients on maintenance hemodialysis in a tertiary care hospital. Materials and Methods:This study was carried out retrospectively on patients undergoing hemodialysis whose samples were received for Hepatitis C screening in the A total of 910 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…3 In our study anti-HCV antibodies were found in 28.8% of patients. This is lower than studies conducted by Rawat 3,7,[9][10][11] Worldwide prevalence rate ranging from 4-15% for HBsAg in HD patients has been reported, whereas, in India it ranges from 3.4% to 45%. 4,12 We report 14.8% HBV positivity among HD patients which in agreement with the study conducted by Mittal et al (10.2%), Bhaumika et al (12.1%).…”
Section: Discussioncontrasting
confidence: 59%
“…3 In our study anti-HCV antibodies were found in 28.8% of patients. This is lower than studies conducted by Rawat 3,7,[9][10][11] Worldwide prevalence rate ranging from 4-15% for HBsAg in HD patients has been reported, whereas, in India it ranges from 3.4% to 45%. 4,12 We report 14.8% HBV positivity among HD patients which in agreement with the study conducted by Mittal et al (10.2%), Bhaumika et al (12.1%).…”
Section: Discussioncontrasting
confidence: 59%
“…10 However, this is less than in the intravenous drug users (IDU), 94%. 9 The seroprevalence of Hepatitis C in patients receiving HD in northern and western India 13,14 is reported to be 23% and 2.7% respectively and in Pakistan 15 29.2%. In a systematic review from Middle-East, the highest prevalence was seen in Syria (54%) and Egypt (50%), lowest in Iran (12%) and Lebanon (9%).…”
Section: Discussionmentioning
confidence: 99%
“…The data presented in Table 4 indicate that during the period from 1993 to 2010, the seroprevalence of HCV in HD patients ranged from 12.1% to 46%, [19][20][21][22][23][24][25] whereas studies conducted after 2010 reveal a general decline in prevalence to 12.4%. [26][27][28][29][30] One exception in this regard, however, is a study conducted in Jammu in 2016, which reported a considerably higher prevalence of 31.4%. 31 We speculate that this wide divergence in prevalence could be attributed to a number of contributory factors, including different geographical locations, a different study duration, or differences in the sensitivity and specificity of the methods used for detecting HCV infection.…”
Section: Seroprevalence Of Hcvmentioning
confidence: 99%